The transformation of violent intercommunal conflict - Ryan, Stephen 1956- (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2006)
In recent years there has been a remarkable growth of interest in the concept of conflict transformation and the closely related strategy of grass-roots peace building. Yet there exists no general critical analysis of the concept of conflict transformation in the context of violent inter-communal conflict and the different approaches that can be included in response to this category of dispute. This study offers a comprehensive survey and critical overview of this emerging area. Examining the reasons for the growing interest in the concept of conflict transformation in situations of ethnic conflict, the book explores the different dimensions of transformation. It draws on examples of strategies from a number of situations of 'ethnic conflict', including Northern Ireland, Israel/Palestine, Bosnia, Kosovo, Cyprus, Spain, Sri Lanka and the former Soviet Union , to identify and assess key issues and problems that have emerged, and ultimately to propose a stronger emphasis on the promotion of inter-subjective understanding